Synergistic activity of nilotinib and established chemotherapeutic drugs in imatinib-sensitive and -resistant BCR-ABL-positive cells - Radujković, Aleksandar; Fruehauf, Stefan; Zeller, W. Jens; Ho, Anthony Dick; Topaly, Julian (Cancer chemotherapy and pharmacology, 2010)
We investigated various combination treatment regimens employing nilotinib with established chemotherapeutic agents (daunorubicin, mitoxantrone, etoposide and cytarabine) in imatinib-sensitive and -resistant BCR-ABL-positive cells. Mitoxantrone or cytarabine showed synergism (CI < 1) in combination with nilotinib in imatinib-sensitive LAMA84 cells, whereas in imatinib-resistant LAMA84-R cells synergistic effects could be assessed for daunorubicin, mitoxantrone and etoposide when combined with nilotinib. In both imatinib-sensitive and -resistant K562 cells daunorubicin, mitoxantrone and etoposide demonstrated synergism in combination with nilotinib. Moreover, both daunorubicin and mitoxantrone led to synergistic antiproliferative effects when combined with nilotinib in imatinib-resistant Ba/F3 cells carrying point mutations in the ABL TK domain (E255K, E255V and T315I). Annexin V/propidium iodide staining revealed a significant enhancement of nilotinib-induced apoptosis in imatinib-resistant Ba/F3T315I and LAMA84-R cells upon combination with daunorubicin and mitoxantrone, respectively. Our results demonstrate the efficacy of combination treatment regimens employing nilotinib and established chemotherapeutic agents in improving antileukemic effects in imatinib-sensitive and imatinib-resistant cells. This may be the foundation for further study on the potential of the applied combinations in a clinical setting.
Online veröffentlicht: 28. Oktober 2009
Gesehen am 09.05.2023